The Crocodile by Fyodor Mikhaylovich Dostoyevsky as a St. Petersburg story (remarks on the glossary of allegories in the genre of St. Petersburg story) - Крыстева, Денка (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article discusses Dostoyevsky’s story The Crocodile as an episode in the development of the so-called “St. Petersburg story”, established by Pushkin and Gogol as a specific ideological and fictional genre, connected with the symbolic representation of the St. Petersburg period in Russian history. In the analysis of the title and the exposition of the story, the monster is seen as an allegory of the disquieted political body in Russia following the reforms of 1861. Among the sources of the allegory are the Biblical synonymous use of “Leviathan – Crocodile”, Thomas Hobbes’ s treatise Leviathan, and the Russian Old Believers’ invectives about The Ruler and The Crocodile-State. The analysis suggests that Dostoyevsky translates the political notion of Leviathan as a metaphor of the absolutist social negotiation through the equivalent of the Crocodile, already familiar in Russian collective mentality. In this respect, it is assumed that the story serves as a warning about the dangers resulting from the disquieted political body.